The role of a preschool teacher in arranging children’s activity in exploratory plays - Walęciak, Maja; Wetoszka, Paulina (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Nowadays, it has been stressed that play, which is in the centre of preschool education, contributes to a multilateral and harmonious development of the child’s personality. What may constitute a source of the children’s knowledge of the social, natural and technical world is an exploratory play, which has become the main topic of this paper. The subject matter of the study concerns the role of a preschool teacher in arranging children’s activity as well as some aspects of implementation of an exploratory play in daily teaching and educational work. Our work as early years teachers has made it possible for us to gain valuable research data as well as to fathom out some issues connected with stimulation of children’s exploratory interests, directing children’s activities and provoking children to pose questions. Thanks to that in our everyday work we try to fully satisfy children’s cognitive needs with the use of a range of methods, forms of work and teaching aids. It depends on a preschool teacher (personal aspect) and on a properly arranged environment (organizational aspect) whether exploratory curiosity of a child (strategic aspect) is going to be stimulated, which will confirm children in their belief that experimenting and creating are worth the effort.